Instant Gratification and Overtreating to Be Safe: Perceptions of U.S. Intensive Care Unit Pharmacists and Residents on Antimicrobial Stewardship - Katharina Rynkiewich; Kruthika Uttla; Leila Hojat (MDPI AG, 2022)
Antimicrobial stewardship programs have been associated with numerous impacts on medical practice including reductions in costs, antimicrobial resistance, and adverse events. While antimicrobial stewardship is now considered an essential element of medical practice, the understandings of the value of antimicrobial stewardship among medical practitioners vary. Additionally, non-physician practitioners are regularly left out of antimicrobial stewardship interventions targeting antimicrobial decision-making. Here, we contribute the perspective from resident physicians and specialists in pharmacy regarding their involvement in antimicrobial prescribing. Notably, our semi-structured interviews with 10 residents and pharmacy specialists described their limited autonomy in the clinical setting. However, the participants regularly worked alongside primary antimicrobial decision-makers and described feeling pressure to overtreat to be safe. The clear rationales and motivations associated with antimicrobial prescribing have a noticeable impact on physicians in training and non-physician practitioners, and as such, we argue that antimicrobial stewardship interventions targeting primary antimicrobial decision-makers are missing an opportunity to address the breadth of antimicrobial prescribing culture. By looking at the perspectives and rationales of physicians in training and non-physician practitioners, we can see evidence that the act of antimicrobial prescribing is impacted by individuals on all levels of the hierarchies present in medical practice.